EVALUASI KESESUAIAN RESEP DENGAN STANDAR PELAYANAN MEDIS (SPM) DAN FORMULARIUM JAMKESMAS PADA PASIEN RAWAT JALAN JAMKESMAS DI RSUD PANEMBAHAN SENOPATI BANTUL - , Dian Medisa, dr. Sulanto Saleh Danu SpFk ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Background: Health is the rights of every human being, however in Indonesia there are still many people who have not been able to access health services because their low income. Thatfor government create a program Jamkesmas based on INA-DRG (Indonesia Diagnosis Related Group) to improve the poor access to quality health services. DRG cost was determined based on a clinical pathway according to the Standard Treatment Guidelines (STGâs) hospitals. Physicians are required to prescribe medicine according to the diagnosis and Jamkesmas formulary. In RSUD Panembahan Senopati Bantul some of the Jamkesmas Formulary medicines werenât procured, so need to study the prescriptions compliance with STGs and Jamkesmas formulary. Objective: To know the prescriptions compliance to STGs and Jamkesmas formulary. Methods: cross-sectional observational study, using quantitative data Jamkesmas outpatient prescriptions and documents about medicine stocks, medical records, and also qualitative data with in-depth interviews. Quantitative data obtained prescriptions were calculated using drug use indicators for the percentage of prescriptions compliance, whereas the availability of medicines using table of medicines list. Result: Percentage of prescriptions compliance with STGs in each of 10 diseases in Panembahan Senopati Bantul hospital was very low, started from 24.3% in CHF to 82% in DM diseases. Average number of drugs per prescription was 2.7 and the most of drugs (85.7%) were prescribed by its generic names